2014
DOI: 10.3892/br.2014.385
|View full text |Cite
|
Sign up to set email alerts
|

Induction of caspase cascade pathway by kaempferol-3-O-rhamnoside in LNCaP prostate cancer cell lines

Abstract: Abstract.Prostate cancer has become a leading cause of mortality in humans. Previous studies have shown the potential anticancer properties of kaempferol-3-O-rhamnoside in breast cancer cell lines. In the present study, the anticancer potential of kaempferol-3-O-rhamnoside was investigated in LNCaP human prostate cancer cell lines. The inhibition of cell proliferation was investigated using MTT assays, whereas its ability to induce the caspase-cascade pathway was investigated by western blotting. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 6 publications
5
26
1
Order By: Relevance
“…The results using S. wallichii extract were similar to those of Halimah et al [24] who showed that the major compound (kaempferol-3-Orhamnoside) in the ethylacetate fraction of. S. wallichii inhibited MCF-7 cell growth via activation of caspase-9 and caspase-3, inducing apoptosis.…”
Section: Discussionsupporting
confidence: 87%
“…The results using S. wallichii extract were similar to those of Halimah et al [24] who showed that the major compound (kaempferol-3-Orhamnoside) in the ethylacetate fraction of. S. wallichii inhibited MCF-7 cell growth via activation of caspase-9 and caspase-3, inducing apoptosis.…”
Section: Discussionsupporting
confidence: 87%
“…In a similar fashion, treatment with kaempferol inhibited proliferation of gastric cancer cell lines MKN28 and SGC7901 through multiple mechanisms; it (a) induced apoptotic cell death, (b) exhibited cell cycle arrest, (c) suppressed tumor growth, (d) decreased cyclin B1, Cdk1, and Cdc25C expressions, (e) lowered Bcl‐2 and enhanced Bax expressions, (f) upregulated cleaved caspase‐3 and ‐9, (g) promoted Poly (ADP‐ribose) polymerase (PARP) cleavage, and (h) decreased p‐Akt, p‐ERK and cyclooxygenase‐2 (COX‐2) expression levels (Song et al, ). Furthermore, kaempferol‐3‐ O ‐rhamnosidedose, a derivative of kaempferol, suppressed cell proliferation rate, induced caspase‐cascade pathway, upregulated the expression of caspase‐3, caspase‐8, caspase‐9, and PARP proteins in LNCaP human prostate cancer cell lines in a concentration‐dependent manner (Halimah et al, ).…”
Section: Health Perspectivesmentioning
confidence: 99%
“…Recent in vitro and in vivo studies have shown the antiproliferative and proapoptotic activities of KMF against various types of cancers including breast (Azevedo et al, 2015;Kim, Hwang, & Choi, 2016;Liao et al, 2016), ovarian (Luo, Rankin, Li, Depriest, & Chen, 2011), lung (Kuo et al, 2015), pancreas (Zhang, Chen, Li, Chen, & Yao, 2008), esophagus (Yao et al, 2016), stomach , colon , prostate (Halimah et al, 2015), bladder (Dang et al, 2015), kidney (Song et al, 2014) and others. Most of these studies demonstrate that the mechanism of KMF is dependent on the inhibition of proliferation of various cancer cells either via cell cycle arrest or induction of apoptosis (Kuo et al, 2015;Liao et al, 2016).…”
Section: Cell Cycle Arrest and Apoptosis By Kaempferolmentioning
confidence: 99%